Learning Through Digital Stories for Safe School Environment - Akdag, Sahin; Altinay, Zehra (Frontiers in Psychology, 2021)
The aim of this study is to evaluate the impact of digital stories in learning based on the theme of safe schools and to examine perceptions of special need education on safe schools. Trainings were carried out with informative videos created through the Distance Education Cen-ter (UZEBIM) for principals and responsible teachers, and the effectiveness of this process was evaluated through reflective opinion forms used. In addition to this, evaluation form was con-ducted to prospective special education teachers in order to evaluate digital stories on safe schools. Also 100 prospective teachers become participants to evaluate the impact of digital stories on their learning about safe schools. Digital stories about safe school become an important source of information in creating a safe school more rapidly and efficiently. In line with the interviews, it was observed that awareness of safe schools was increased and digital dimensions of safe schools were internalized through digital stories. With this awareness in the Covid 19 process, it was revealed that the schools did not have sufficient safe school characteristics and all stakeholders should take preventive measures in coordination in order to establish a safe school environment.